Clinical and evolving features of women diagnosed with precancerous cervical lesions, screened and treated in the Amazon region of Brazil - Patricia Rezende do Prado; Rosalina Jorge Koifman; Ilce Ferreira da Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The objective of the study was to determine the dynamics of precancerous lesions in women of a cohort treated for cervical intraepithelial neoplasia (CIN) and followed up over the next two years. The conditional probability of failure was calculated using the Kaplan-Meier method, and the raw and adjusted hazard ratios (HR) were determined using Cox regression with a p-value entry of < 0.05. Of the 237 women who were treated, 51.5% were accompanied over 24 months, and treatment failed for 21.9% of those accompanied. Women who had five or more pregnancies (adjusted HR = 3.10, 95%CI: 1.28-7.51) or an initial histological diagnosis of CIN II/III demonstrated an independent risk of treatment failure (adjusted HR = 3.14, 95%CI: 1.20-8.19). Being in a stable relationship was a protective factor against treatment failure (adjusted HR = 0.47, 95%CI: 0.24-0.89). A history of more frequent pregnancies and a histological diagnosis of CIN II/III are directly correlated with risk of CIN treatment failure, whereas being in a stable relationship is inversely correlated with this risk.